Implementation of Biopore Infiltration Holes (LBR) for the Reduction of Organic Household Waste: A Literature Review - Sy, Asmalinda; Barlian, Eri; Yuniarti, Elsa; Handayauni, Linda (Jurnal Kesehatan Cendikia Jenius, 2025)
Household waste management is a significant environmental challenge, especially in urban areas with rapid population growth. If not handled properly, organic waste can cause various problems, such as environmental pollution, increased greenhouse gas emissions, and the buildup of loads in landfills. This article aims to describe the implementation of biopores to reduce household organic waste. The method used is qualitative and literature review. A total of 10 articles from the Garuda database were analyzed in this study with the criteria published in 2017-2023, using the keywords “biopori, household organic waste”. The results of this study show that organic waste in biopore holes undergoes a natural decomposition process through the help of microorganisms in the soil so that it has a positive impact that can reduce household waste, namely the formation of compost, and fertilize the soil.conclusion : The implementation of biopores effectively reduces household organic waste through decomposition and compost formation. Recommendations The implementation of biopores should be expanded to reduce organic waste and sustainably improve soil fertility.